Integrated humification of poultry waste - Mushtaq, Maryam; Iqbal, MK; Nadeem, A; Khan, RA (Bangladesh Journal of Scientific and Industrial Research, 2018)
In this study effects of adding chemical and microbial agents in the humification process of poultry wastes were carried out. Chemicals and microbes play a vital role to accelerate the humification process. Salmonella and lime were applied individually to observe the variation in maturity and stability parameters like degree of polymerization (DP), C/N, humification rate (HR), humification index (HI), cation exchange capacity (CEC), and nitrate nitrogen concentration of the humified poultry wastes. Thus it was acclaimed that the microorganisms Salmonella encourage the compost formation where as humification with lime proceeded relatively with a lesser time than Salmonella. Furthermore, the decline in carbon and nitrogen ratio and increase in CEC, DP, HR, HI, potassium and phosphorous were recognized in a higher scale in chemically treated wastes compared to that of microbial one. It was concluded that use of chemicals reduce the quantum of waste in minimum time. Bangladesh J. Sci. Ind. Res.53(4), 283-288, 2018